Losses Induce Consistency in Risk Taking Even Without Loss Aversion. (9th October 2011) - Yechiam, Eldad; Telpaz, Ariel
ABSTRACT It is posited that because of the attentional effect of losses, individuals would show more behavioral consistency in risk‐taking tasks with losses, even in the absence of loss aversion. In two studies, the consistency of risky choices across different experience‐based tasks was evaluated for gain, loss, and mixed (gain loss) tasks. In both studies, losses facilitated the consistency across tasks: the correlation between risk‐taking choices in different tasks increased when the tasks involved frequent losses. Study 2 also showed a positive effect of losses on temporal consistency. Losses increased the correlation between risk‐taking levels across two sessions that were 45 days apart. Also in Study 2, losses induced consistency between experiential risk‐taking choices and self‐reported ratings of risky behavior. In both studies, the positive effect of losses on consistency was observed even when the average participant did not exhibit loss aversion. Taken together, the results indicate that losses increase the consistency of risk‐taking behavior and suggest that this is due to the effect of losses on attention. Copyright © 2011 John Wiley & Sons, Ltd.